PERBANDINGAN EFEKTIVITAS EKSTRAK KULIT MANGGIS (GARCINIA MANGOSTANA L.) SEBAGAI AGEN PELINDUNG KULIT DARI SINAR UVA DAN UVB PADA MENCIT PUTIH (MUS MUSCULUS) - LIA NASTI; RIRI ARISANTY SYAFRIN LUBIS (LP2MTBM MAKARIOZ, 2023)
Indonesia is a country which has a tropical climate which is filled with an abundance of sunlight every year. UVB rays have the ability to cause sunburn greater than UVA rays. UVA rays themselves have the ability to penetrate deeper layers of the skin and can also damage DNA from the skin indirectly which can cause photo aging of the skin. To examine the effect of mangosteen rind extract (Garcinia mangostana L.) as a protective agent from UVA and UVB rays in white mice (Mus musculus). This type of research is a true experimental study with a post-controlled group design, namely the type of research that observes the control group and the treatment group after the action. The value in each group was p<0.05, which means that there were significant differences in each treatment group for all observations. Each dose of mangosteen rind (Garcinia mangostana L.) semanggi extract with high levels of redness or erythema on the skin of experimental animals will disappear. Keywords: UVA, UVB, Mangosteen Peel Extract, Skin Protector